2012
DOI: 10.1371/journal.pgen.1003069
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-Specific Regulation of Chromatin Insulator Function

Abstract: Chromatin insulators organize the genome into distinct transcriptional domains and contribute to cell type–specific chromatin organization. However, factors regulating tissue-specific insulator function have not yet been discovered. Here we identify the RNA recognition motif-containing protein Shep as a direct interactor of two individual components of the gypsy insulator complex in Drosophila. Mutation of shep improves gypsy-dependent enhancer blocking, indicating a role as a negative regulator of insulator a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
103
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(111 citation statements)
references
References 58 publications
7
103
0
1
Order By: Relevance
“…They can, however, mediate homotypic and heterotypic protein-protein interactions via their BTB/POZ (Broad complex, Tramtrack, Bric-a-brac)/(Poxvirus and Zinc finger) domains. The third group includes biochemically diverse proteins: Elba1, Elba2, Elba3, and Shep (Aoki et al 2012;Matzat et al 2012). Though not required for enhancer blocking, these proteins appear to modulate the enhancer-blocking ability of insulator elements in a tissue-or stage-specific manner.…”
mentioning
confidence: 99%
“…They can, however, mediate homotypic and heterotypic protein-protein interactions via their BTB/POZ (Broad complex, Tramtrack, Bric-a-brac)/(Poxvirus and Zinc finger) domains. The third group includes biochemically diverse proteins: Elba1, Elba2, Elba3, and Shep (Aoki et al 2012;Matzat et al 2012). Though not required for enhancer blocking, these proteins appear to modulate the enhancer-blocking ability of insulator elements in a tissue-or stage-specific manner.…”
mentioning
confidence: 99%
“…For example, collected embryos from population cages have been used very successfully in immunoprecipitation assays [6][7][8] , mass collection of larval tissues from dissociated larvae has demonstrated to be a very good source for 3C experiments 4 and RNA preparations 15 , and heads from adult flies have been utilized for ChIP experiments 16 . In addition, adults are often needed to make fly extracts for tissue culture 17 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies often require large amounts of biological material, not only from adult flies, but also from larvae 4 , pupae 5 and embryos [6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…However, it has also been suggested that insulator bodies represent storage sites of insulator proteins (Golovnin et al, 2008) or form as a result of certain stress conditions (Schoborg et al, 2013). Although the presence of insulator bodies is not sufficient for insulator activity (Gerasimova et al, 2007;Golovnin et al, 2008), all mutations that are known to alter the integrity of insulator bodies also affect insulator function (Capelson and Corces, 2005;Capelson and Corces, 2006;Gerasimova and Corces, 1998;Ghosh et al, 2001;Golovnin et al, 2012;Lei and Corces, 2006;Matzat et al, 2013;Matzat et al, 2012;Pai et al, 2004). These results suggest that monitoring these structures serves as a useful phenotypic indicator.…”
Section: Introductionmentioning
confidence: 99%
“…In both Drosophila and mammals, genome-wide binding profiles of insulator proteins are largely invariant across cell types (Bushey et al, 2009;Kim et al, 2007), suggesting that the particular higher-order chromatin configurations mediated by insulator proteins might be regulated in different cell types. Recent work has shown that RNA and RNA-binding proteins can modulate the activities of the gypsy insulator (Lei and Corces, 2006;Matzat et al, 2013;Matzat et al, 2012), the Drosophila CTCF insulator complex (Lim et al, 2013;Moshkovich et al, 2011), and mammalian CTCF and its partner cohesin (Sun et al, 2013;Yao et al, 2010). In the case of the RNA-binding protein Alan Shepard (Shep), gypsy insulator activity and insulator body localization is antagonized in a tissue-specific manner (Matzat et al, 2012).…”
Section: Introductionmentioning
confidence: 99%